Semantic Coherence and Verbal Cohesion among “The Verbals of Hell’s Beverage” in Holy Qur’an - Almallah, Aisha Ibraheem (Dirasat: Human and Social Sciences, 2025)
Objectives: The research aims to reveal the semantic coherence aspects among the verbals of Hell’s beverage in Holy Qur’an, that are (Hameem) Scalding, (Ghassaq) Liquefied, (Sadeed) Pus, (Shawb) Mixture and (Maa’ KalMohl) Water like molten metal. Methods: The research employed an inductive method to identify terms in the Quran that describe the drinks of the people of Hellfire, and then analyzed them using a descriptive-analytical approach. This analysis focused on the context to elucidate meanings and characteristics of these terms. The study utilized a modern linguistic perspective on coherence and textual consistency to measure the semantic and verbal coherence within the Quranic text. Results: The results revealed three aspects of semantic coherence: contextual meanings (intense heat, boiling, mixing, viscosity, and darkness), structural semantic meanings (abundance, intensity, permanence, continuity, and necessity), and contextual semantic meanings (denoting and defining, universalizing the genus name, confirming the term's meaning, and clarifying its reality). Consistency was evident in two aspects: repetition and congruence. Through congruence, several relationships were identified: generic, associative, attributive, and similitude. These relationships supported the coherence and continuity of meanings in the Quranic text. The study concluded that the terms for the drinks of the people of Hellfire are coherent and consistent. They all refer to a single type of drink, with variations in names. Conclusions: There is a need for further applied studies of the science of text analysis in the Quran, as it enables the discovery of new results in the field of interpretation.